4(2)-y=-6

Simple and best practice solution for 4(2)-y=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2)-y=-6 equation:


Simplifying
4(2) + -1y = -6

Multiply 4 * 2
8 + -1y = -6

Solving
8 + -1y = -6

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + -1y = -6 + -8

Combine like terms: 8 + -8 = 0
0 + -1y = -6 + -8
-1y = -6 + -8

Combine like terms: -6 + -8 = -14
-1y = -14

Divide each side by '-1'.
y = 14

Simplifying
y = 14

See similar equations:

| -25=5/6n | | 8m-22/17=2 | | 7m-3-6=6 | | -37-2x=-3(-8x-5) | | -x/24 | | 3(3-2b)-3(3b-6)=-48 | | 50t+55t=630 | | 17+d=50 | | Y-8=5/2(x-6) | | cos(2x)+3cos(x)-4=0 | | (1,3),m=-3/4 | | -2ysquared+3ysquared= | | x+9=y-5 | | 3x^2-x-102=0 | | -6=2(p-3)+4(p+6) | | 5/6x-1/2=3/4x | | 851/0.9 | | -1-(8y-2)=5(2y-7) | | 7.34-y=9.06 | | K/6.2=1.5 | | 81=t+5 | | (4x-8)(7x+6)=0 | | -2x+6=-5x-4 | | 4x+2(3x-1)=-52 | | 6p-7q=18 | | 98=n+42 | | 48=2 | | 6/-3=-7 | | 7(3x+1)=5x-9x | | Y+3=-10 | | 4+w=32 | | (-5x^3+4x^5+6)= |

Equations solver categories